PyrroTriPol: a semi-rigid trityl-nitroxide for high field dynamic nuclear polarization. Issue 14 (20th March 2023) - Halbritter, Thomas; Harrabi, Rania; Paul, Subhradip; van Tol, Johan; Lee, Daniel; Hediger, Sabine; Sigurdsson, Snorri Th.; Mentink-Vigier, Frédéric; De Paëpe, Gaël
Abstract : A semi-rigid trityl-nitroxide polarizing agent is introduced for magic angle spinning (MAS) dynamic nuclear polarization (DNP), which significantly broadened the scope of solid-state NMR to study biomolecular systems and materials. Abstract : Magic angle spinning (MAS) dynamic nuclear polarization (DNP) has significantly broadened the scope of solid-state NMR to study biomolecular systems and materials. In recent years, the advent of very high field DNP combined with fast MAS has brought new challenges in the design of polarizing agents (PA) used to enhance nuclear spin polarization. Here, we present a trityl-nitroxide PA family based on a piperazine linker, named PyrroTriPol, for both aqueous and organic solutions. These new radicals have similar properties to that of TEMTriPol-I and can be readily synthesized, and purified in large quantities thereby ensuring widespread application. The family relies on a rigid bridge connecting the trityl and the nitroxide offering a better control of the electron spin–spin interactions thus providing improved performance across a broad range of magnetic fields and MAS frequencies while requiring reduced microwave power compared to bis-nitroxides. We demonstrate the efficiency of the PyrroTriPol family under a magnetic field of 9.4, 14.1 and 18.8 T with respect to TEMTriPol-I. In particular, the superiority of PyrroTriPol was demonstrated on γ-Al2 O3 nanoparticles which enabled the acquisition of a high signal-to-noise surface-selective 27 Al multiple-quantum MAS experiment at 18.8 T and 40 kHz MAS frequency.